SISTEM PENUNJANG KEPUTUSAN PENENTUAN KONSUMSI BUAH SESUAI DENGAN KONDISI TUBUH MENGGUNAKAN METODE RULE BASED SYSTEM - Bagus Satrio Utomo; Mahmud Yunus; Liduina Asih Primandari (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2025)
Fruits are vital sources of vitamins and minerals that aid in detoxification and overall fitness. Kedai Jus Sarjana provides various processed fruit juices; however, customers often purchase drinks based on preference without understanding their specific nutritional benefits. This study aims to enhance the shop’s service by developing a web-based Decision Support System (DSS) to recommend juices based on the customer’s physical condition. The system utilizes a Rule-Based System algorithm to determine the best fruit choices according to the symptoms or health complaints inputted by the user. Designed using UML modeling and MySQL databases (CDM/PDM), the application is multi-platform and accessible via web browsers. The result provides an alternative health-consultation service, offering customers personalized fruit recommendations and detailed information regarding the nutritional content and benefits of each juice for their specific needs.